PERFIL DE GESTANTES SUBMETIDAS À TRIAGEM DO VÍRUS HTLV NO MARANHÃO - de Souza, Verônica Guimarães; Serra e Silva, Camila Moreira; Pires, Claudyene; Mochel, Elba Gomide; Martins, Christiane de Sousa; Gomes, Samea Cristina (Revista Baiana de Enfermagem‏, 2012)
OBJETIVOS: Avaliar o perfil epidemiológico das gestantes submetidas à triagem para o vírus HTLV 1 e 2, atendidas no pré-natal de três serviços públicos. METODOLOGIA: Estudo transversal realizado entre 11/02 e 03/12/2008, com 2044 gestantes em três serviços públicos de pré-natal, São Luis/MA. As pacientes foram orientadas sobre o estudo, incluídas após assinatura do TCLE e preenchimento do questionário. Participaram gestantes entre 18 e 45 anos sem história de doenças psiquiátricas, hipertensão arterial, nefropatia, diabetes e outros que caracterizassem necessidade de pré-natal especializado. A amostra foi calculada em 2041, poder do teste 95%, erro absoluto de 5%, foi usado programa Stata 9.0, realizado teste qui quadrado e aceito p<0,05 (95%) como limite para significância. O projeto foi aprovado pelo CEP/UFMA (Parecer Nº568/2007). RESULTADOS: A média de idade foi de 25 anos, 35,12% são solteiras com companheiros, 41,10% de cor da pele parda, 57,19% com ensino médio completo, 54,21% iniciaram atividade sexual ente 15 e 18 anos, 35,08% nunca usam preservativo em relações sexuais; 54,99 são primigestas, 15,22% foram amamentadas pelas mães e outras pessoas. 42,51% já tiveram filhos, destas 31,9% já praticaram aleitamento cruzado. 1,2% já usaram drogas ilícitas e 9,4% têm/tiveram relacionamento com parceiros usuários de drogas. CONCLUSÃO: A amostra revelou que as gestantes apresentam características que justificam a triagem do vírus HTLV 1 e 2 durante o pré-natal, no entanto são necessários mais estudos para avaliação da real situação no Estado do Maranhão. ABSTRACT INTRODUCTION: HTLV is a retrovirus with tropism by T- lymphocytes; kind 1 is endemic in the Caribbean region, Japan, South America, and parts of Africa; kind 2 is found in some native American groups, rarely in Africa, and in Europe it is associated to the use of injectable drugs, and it prevails more in Brazilian indigenous populations. In Brazil it is estimated that 2.5 million people are infected in all the states researched, with different prevalence. The virus is transmitted through breast feeding, sexual contact without protection, blood transfusion, and by sharing contaminated syringes. The infection though HTLV-1 is associated to T- Cells Lymphoma of the adult and Chronic Degenerative Neurologic Syndrome. The diagnosis of the infection by the virus is made through the identification of anti-bodies anti-HTLV-1 and 2 (ELISA) and confirmatory tests, being Western Blot the most used one, however, PCR is the gold standard. OBJECTIVES: To evaluate the epidemiologic profile of pregnant women submitted to the classification for the virus HTLV-1 and 2, assisted during prenatal care at three public services. METHODOLOGY: Transversal study executed between Feb/11 and Dec/03/2008, with 2044 pregnant women at three public service of prenatal care, São Luis/MA. The patients were guided about the study, included after signing the TCLE and filling in a questionnaire. The pregnant women who took part of it were between 18 and 45 years old without psychiatric diseases background, high blood pressure, nephropathy, diabetes and others that characterize specialized prenatal care needs. The sample was calculated in 2041, test power 95%, absolute mistake of 5%, Stata 9.0 program was used, Chi Square test was taken, and p<0,05 (95%) was accepted as the limit for significance. The Project was approved by CEP/UFMA (Opinion Nº568/2007). RESULTS: The average age was 25 years old, 35.12% are single with partners, 41.10% have olive skin, 57.19% have finished high school, 54.21% started sexual activity between 15 and 18 years old, 35.08% have never used condom during sexual intercourse; 54.99 are primiparous women; 15.22% were breast fed by their mothers and other people. 42.51% have already had children, out of these, 31.9% have already practiced crossed breast feeding. 1.2% have already used illegal drugs, and 9.4% have/have had relationship with drug users. CONCLUSION: The sample revealed that the pregnant women presented characteristics that justify the classification of virus HTLV-1 and 2 during the prenatal care, however more studies are necessary for the evaluation of the real situation in the State of Maranhão.